Humanist Education the Dayak of Kalimantan Indonesia Islamic Perspective - Sudarno Shobron; Trisno; Muthoifin; Mahmudulhassan; Muh. Nur Rochim Maksum (Walidem Institute and Publishing (WIP), 2023)
This research aims to find a model of human Islamic education for the Dayak Bakumpai tribe in Puruk Cahu, Murung Raya Regency, Central Kalimantan, and factors that support and hinder the implementation of humanism Islamic education. This research was qualitative research using the field study method. Data were collected through observation, field interviews, and documentation in the form of manuscripts and articles related to the research's subject. The object of this research was Islamic education institutions comprised of formal, non-formal, and informal education institutions. The research subjects were Islamic religious teachers, preachers, Bakumpai Dayak people, and religious leaders. The approach used was ethnography-phenomenology, emphasizing studying and interpreting the nomenclature of the Dayak ethnic group. The analysis was done using descriptive analysis, which looks for correlation and significance between the data collected to arrive at results that are in line with the predicted outcomes. The findings of the research indicate that the humanism Islamic education model of the Dayak tribe can be divided into three categories: (1) formal education; at SMA Muhammadiyah, this was accomplished through a self-development program in the form of extracurricular activities such as the martial arts Tapak Suci, Hizbul Wathon, and counselling and guidance. (2). Non-formal education; at Pondok Pesantren Karya Pembangunan in the form of Speech training, Nasyid, Habsyi, and leadership training. (3). Informal education; in the form of arisan (a kind of social gathering activity), community development for converts, and religious lectures in mosques. Humanism Islamic education was influenced by several factors, such as Sufism, immigrants, trade, and marriage.